Characteristics and Prognostic Value of Papillary Histologic Subtype in Nonmetastatic Renal Cell Carcinoma in Korea: A Multicenter Study - Lee, Won Ki; Lee, Sang Eun; Hong, Sung Kyu; Jeong, Chang Wook; Park, Yong Hyun; Kang, Seok Ho; Kim, Yong-June; Hong, Sung-Hoo; Choi, Won Suk; Byun, Seok-Soo (Urology Journal, 2014)
Purpose: To analyze the characteristics of nonmetastatic papillary renal cell carcinomas (RCC) and the prognostic value of RCC histologic subtyping, based on a large multicenter experience in Korea. Materials and Methods: A total of 2,905 patients with nonmetastatic RCC (TxN0M0) at the time of surgery were retrospectively enrolled from five institutions between 1999 and 2011 in Korea. Among these, patients with clear cell subtype (n = 2,488, 85.6%) and papillary subtype (n = 192, 6.6%) were included in our study. Results: Patients with papillary subtype did not differ significantly from those with clear cell subtype on the following parameters: age (P = .694), gender (P = .511), body mass index (P = .136), patient performance status (P = .419), symptoms at presentation (P = .419), tumor size (P = .778) and pathologic stage (P = .367). However, high Fuhrman’s grades were more common in papillary subtypes compared with clear cell subtypes (P = .001). The 5-year recurrence-free survival rates in patients with clear cell subtype and papillary subtype were 84.9% and 86.7%, respectively (P = .167). The 5-year cancer-specific survival rates in patients with clear cell subtype and papillary subtype were 92.0% and 93.1%, respectively (P = .931). Histologic subtype was not an independent prognostic factor of recurrence-free and cancer-specific survival (P = .107 and P = .998, respectively). Conclusion: Our study suggests that the characteristics and prognosis of papillary subtype might be comparable to those of clear cell subtype in non-metastatic renal cell carcinoma, especially in Asia.